Nonlinear oscillations of the absolute elastic weightless string. Asymptotics construction - Krylovas, Aleksandras; Miškinis, Paulius (Lietuvos matematikos rinkinys, 2007)
The mathematical model of string nonlinear oscillations is presented. To find the asymptotic solution of the problem an averaging scheme is constructed.